Spectroscopy techniques and the measurement of molecular radical densities in atmospheric pressure plasmas - Peverall, R; Ritchie, G (IOP Science, 2019)
Cold atmospheric pressure plasmas (CAPs) are finding an increasing number of applications in diverse fields such as sterilization, medicine and dentistry, because they induce chemical reactivity at near-ambient temperature. These plasmas are usually generated in noble gas flows which propagate into air, resulting in the production of a wide variety of species which can cause primary and secondary chemistry in both the gas and liquid phases. Detailed understanding of this low temperature reactivity requires selective and sensitive measurements of radical species. In this review we focus upon several techniques from a methodological point of view that are suitable for the sensitive detection of reactive species, or show promise for this purpose. A range of traditional and contemporary spectroscopic methods for measuring across different phases is highlighted in an attempt to present a 'detection landscape' for CAP-borne radicals.